TINJAUAN KRIMINOLOGI TERHADAP KENAKALAN REMAJA (JUVENILE DELIQUENCY) DAN PENCEGAHANNYA DITINJAU DARI UU PERLINDUNGAN ANAK - Sinaga, Lestari Victoria; Kaban, Jhon Rico; Supratman, Eddy (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2020)
This study aims at finding the causes influencing the emergence of juvenile delinquency, the factors driving the emergence of mass fights among adolescents, and How to deal with juvenile delinquency and mass fights between groups. This research is a normative juridical method, namely Legal Research conducted by examining library materials or secondary data. The results show that factors causing juvenile / juvenile delinquency, among others, are psychiatric or psychological factors and family structure. Mass fighting is one form of juvenile delinquency, where there are two contributing factors, namely internal factors (from within) and external factors, namely environmental factors (family, school and community). While specific factors for example to show a sense of solidarity and loyalty from friends (who tend to be inconsequential), defending the good name of the school, negative competition, lack of transportation facilities, the complexity of big city life, showing hard films on television and so on.